Characterization and documentation of genetic resources utilizing multimedia databases: Proceeding of a workshop, 19-20 December 1996, University of Naples Federico II, Naples, Italy - Puzone, L.; Hazekamp, Thomas; International Plant Genetic Resources Institute (1998)
Advances in information technology have brought image processing and analysis increasingly closer to practical application in a variety of professional fields including plant genetics resources. The University of Naples Federico II, Faculty of Agriculture, Dept. of Agronomy and Plant Genetics, in collaboration with IPGRI, organized a two day workshop on image based information technology and its application in plant genetic resources documentation and related fields. The aim of the workshop was to present a series of different approaches to the characterization and documentation of genetic resources using images or image processing. The workshop was divided into two parts; one dealing with the presentation of systems for the documentation of genetic resources by means of images and a second one devoted to some approaches to image analysis and processing.